Social Marginalization of Patients with Ostomy: A Content- Based Analysis - Nasrin Sarabi; Hasan Navipour; Easa Mohammadi (Iran University of Medical Sciences, 2015)
Background: A few studies have addressed the impact of stoma on patients' social life. This study aimed to understand the problems leading to social isolation of patients undergoing ostomy. Methods: A conventional qualitative content analysis by unstructured interviews was conducted on 27 patients with intestinal or urinary diversion ostomy recruited from the Iranian Ostomy Association (IOA) with purposive sampling since March to October. Results: The findings showed some concerns after ostomy. These concerns lead to patient's isolation in 4 main categories of "sense of exclusion", "helplessness in controlling unpleasant side effects", "weakness in informing patients", and " no support". Conclusion: Educational, financial, and cultural support of the patients undergoing ostomy can prevent their social.